Developing Canva-Based Interactive Worksheet Integrated ‎with Liveworksheets for Teaching Expository Text ‎ - Galuh Dwi Ajeng; Futri Rahayu; Hajjah Zulianti; Aksendro Maximilian (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to develop a Canva-based interactive worksheet integrated with Liveworksheets for teaching expository text to tenth-grade students of SMAN 14 Bandar Lampung, to determine its feasibility through expert validation, and to identify students’ responses to the developed product. This study employed the Research and Development (R&D) method using the ADDIE instructional design model, covering the Analysis, Design, Development, Implementation, and Evaluation stages. The participants were the tenth-grade students. Data were collected through interviews, questionnaires, and expert validation sheets. The developed product combined Canva for designing instructional content and visual layout with Liveworksheets for creating interactive activities, including drag-and-drop, matching, multiple-choice, and short-answer exercises. Before implementation, the product was revised based on suggestions from material, media, and language experts. The validation results indicated that the product was highly feasible, with mean scores of 4.88, 4.71, and 5.00 from the material, media, and language experts, respectively, resulting in an overall mean score of 4.86 (“very good”). Students reported highly positive responses during the field trial (96.52%) and questionnaire (96.65%), indicating favorable perceptions of the developed worksheet. These findings indicate that the developed worksheet is feasible and perceived as practical for use in the participating class; however, its effectiveness in improving learning outcomes and its applicability to other educational contexts require further investigation.